Implikasi Pelaksanaan Mediasi Sengketa Akibat Perceraian Terhadap Perlindungan Hak Mantan Istri Dan Anak Di Pengadilan Agama Lebong - Alamsyah, Agus (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: In an effort to optimize mediation as a means of resolving civil disputes, especially divorce cases and disputes resulting from divorce, mediators at the Lebong Religious Court should always strive for two disputing parties to take a peaceful route, because a peaceful route will speed up dispute resolution. The implementation of mediation also needs to be maximized because if the parties do not reach an agreement to live in harmony again, mediation can continue with disputes resulting from divorce. This research aims to determine the implications of implementing dispute mediation resulting from divorce on the rights of ex-wives and children at the Lebong Religious Court. The research method used is descriptive qualitative by collecting information from primary data sources and secondary data sources, reviewing and analyzing according to the topic discussed in this research. The results of this research show that there are implications for implementing dispute mediation resulting from divorce on the rights of ex-wives and children at the Lebong Religious Court, one of which is fulfilling the rights of ex-wives and children after divorce.Key words: mediation, dispute, consequences of divorce. Abstrak : Dalam upaya mengoptimalkan mediasi sebagai sarana penyelesaian sengketa perdata khususnya perkara perceraian dan sengketa akibat perceraian para mediator di Pengadilan Agama Lebong sudah seharusnya selalu mengupayakan dua pihak yang bersengketa untuk menempuh jalur damai, karena jalur damai akan mempercepat penyelesaian sengketa. Mediasi juga perlu dimaksimalkan penerapannya karena apabila para pihak tidak mencapai kesepakatan untuk hidup rukun kembali, mediasi dapat dilanjutkan dengan sengketa akibat perceraian. Penelitian ini bertujuan untuk mengetahui implikasi pelaksanaan mediasi sengketa akibat perceraian terhadap hak mantan istri dan anak di Pengadilan Agama Lebong. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan mengumpulkan informasi dari sumber data primer dan sumber data sekunder, mengkaji, dan menganalisa sesuai dengan topik pembahasan dalam penelitian ini. Hasil dari penelitian ini, terdapat implikasi pelaksanaan mediasi sengketa akibat perceraian terhadap hak mantan istri dan anak di Pengadilan Agama Lebong, salah satunya terpenuhinya hak mantan istri dan anak pasca perceraian.Kata kunci: mediasi, sengketa, akibat perceraian.